KAJIAN LITERATUR SISTEM INFORMASI MANAJEMEN STOK - Putra, Guntur Maulana; Nurul Huda, Sheila (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
Information systems have a big role in the needs of a company, information systems optimize the business world, especially now with the increasingly advanced development of science and technology, the role of information systems has a big influence on the progress of a company or business. The research entitled "Optimizing Information Systems in Rural Iron Shops: Challenges, Analysis and Solutions" is intended to provide information regarding the optimization of information systems by providing solutions which are of course useful, especially for Rural Iron Shops. This research uses qualitative descriptive writing with library research methods. by reviewing various bibliographic source journals.